Intraperitoneal antibiotic utilization among continuous ambulatory peritoneal dialysis (CAPD) patients with peritonitis at a tertiary hospital setting in Malaysia - Ahmad, Mastura; Zin, Che Suraya; Ab Rahman, Ab Fatah (Wolters Kluwer Health, 2020)
Introduction: Patients receiving continuous ambulatory peritoneal dialysis (CAPD) are commonly associated with peritonitis. However, little is known about the utilization of antibiotics for the treatment of peritonitis in these patients. Objectives: This study aimed to evaluate the patterns of intraperitoneal (IP) antibiotic utilization for the treatment of peritonitis in CAPD patients. Materials and Methods: This is a retrospective study conducted at a tertiary hospital setting in Malaysia. Medical records of CAPD patients who were diagnosed with peritonitis and registered with National Kidney Registry from 2013 to 2018 were reviewed. Types of antibiotics used and its dose and duration were recorded and reported using the anatomical therapeutic chemical/defined daily dose (ATC/ DDD) system. Results: A total of 105 peritonitis episodes were recorded from 72 patients. The most common first-line empirical antibiotic combinations used were ceftazidime/cefazolin (40%, n = 42), followed by cefepime/cefazolin (30.5%, n = 32) and ceftazidime/cloxacillin (25.7%, n = 27). The definitive therapy for culture-proven CAPD-related peritonitis (CAPD-P) showed that vancomycin was the most frequently prescribed antibiotic (31.7%, n = 26/82), followed by amikacin (14.6%, n = 12/82), meropenem (11%, n = 9/82) and ampicillin (11%,n = 9/82). Ciprofloxacin was among the least prescribed definitive antibiotics for CAPD-P (2.4%, n = 2/82) but the DDD/100 patient-days estimates showed that it had the highest therapeutic intensity. Conclusion: There are various IP antibiotics used for CAPD-P and the most common empirical therapy was the combination of ceftazidime and cefazolin while vancomycin is predominantly used for definitive therapy. Future studies to evaluate the clinical outcomes of the antibiotic use should be conducted to have a better insight on the efficacy of the peritonitis treatment.